Plan de negocios para la implementación de las nuevas gasolinas en la estación de servicio “Corazón De Jesús”. - Ordóñez Ordóñez, Jessica Gissela (2023)
The current work titled as: Businesses Plan for the new gasolines implementation in the "Corazón de Jesús" Service Station, was made with the purpose by knowing how feasible and opportune, it will be to commercialize the new fuels, such as ECOPLUS gasoline (89 octane), being a substitute product from EXTRA gasoline (85 octane) and PREMIUN gasoline (95 octane), being the SUPER gasoline replacement (92 octane). The methodology had a quantitative approach a descriptive type, the selected sample corresponds to 353 clients, to whom were applied a population 4345 clients survey, what are registered in the database this gas station. It was made the demand calculation according to average sales historical data from last three years. It was developed the market study, the technical study and finally, the financial study, the taken data for making the calculations were taken from true sources from the Service Station, also at sources from the Government, by knowing the inflation rate and the rate WTI, for setting fuel prices. The results, which emerged, through the got different calculations do not reveal, what the project presented a TMAR 11.69%, a VAN $4,956.40 with a 14% TIR, which into comparison to the bank interest rate 11.30%, it presents, that the project is feasible to implement in this Service Station. Furthermore, based on the made surveys, they also present with favorable results, by presenting with a 61% acceptance at consuming these new fuels, which is why at the time, at commencing distribution these gasoline’s to the commercialization this Service Station, it could already have a consideration selling these new products.